Influence of Norplant on T3, T4 and TSH concentration in acceptor in endemic goiter area - Zainal Arifin Nang Agus Zainal Arifin Nang Agus (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
Norplant contains a potent progesteron, namely levonorgestrel. It induces iodine excretion in urine and simultaneously stimulates the thyroid function.The objectives of this study were to examine the T3, T4 and TSH concentration of the Norplant acceptors for 3 months. The subjects were 8 acceptors of Norplant taken from an endemic goiter area in Cangkringan, Sleman, Yogyakarta.The results of this study showed that T3, T4 and TSH were in normal range but they were in the low level. Three months after using Norplant, T3 and T4 level increased, but they are not significant (p>0,05). On the other hand, T4 level decreased significantly (p<0,05). Based on those data, there is an early stage of hipothyroid. It is strongly suggested that it would be much better if similar study could be conducted in longer time period.Key words: Norplant - T3, T4 and TSH - endemic goiter - hypothyroidism